THE EFFECT OF FINANCIAL RATIOS IN PREDICTING FINANCIAL DISTRESS IN MANUFACTURING COMPANIES - Risa Arifiana; Sholikha Oktavi Khalifaturofi'ah (Faculty of Economic and Business, University of Pasundan, 2022)
The purpose of this study is to analyze the effect of financial ratios in predicting financial distress in manufacturing companies. The sampling technique used in this study is purposive sampling. The research sample is 87 manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2020 period. The data analysis technique is logistic regression. The results show that profitability and activity ratio have a negative and significant effect on predicting financial distress. In addition, the liquidity and leverage ratio have no significant effect on predicting Financial Distress. The implication of this study is manufacturing companies have to increase profitability and activity in order to avoid financial distress.